Analisis Nilai Religius dan Nilai Kepahlawanan Pada Novel Sangkakala di Langit Andalusia Karya Hanum Salsabiela Rais dan Rangga Almahendra Sebagai Bahan Pembelajaran Berbasis TPACK di SMA - Fitriawati, Sasi (Universitas Mathla'ul Anwar Banten, 2025)
This study aims to describe the religious and heroic values contained in the novel Sangkakala di Langit Andalusia and to analyze its potential use as Indonesian language learning material based on the TPACK framework at the senior high school level. The research employed a descriptive qualitative method with content analysis techniques. The data consisted of excerpts from the novel containing religious and heroic values, which were then categorized according to predetermined indicators. The results of the study show that the novel Sangkakala di Langit Andalusia contains various religious values, including obedience to God (72 excerpts), optimism (63), courage (59), perseverance (58), solidarity (53), love of knowledge (50), self-sacrifice (49), responsibility (46), sincerity (43), self-confidence (36), discipline (34), honesty (31), respect for others (27), creativity (19), and tolerance (15). The heroic values identified include courage (52 excerpts), self-sacrifice (50), solidarity (53), and perseverance (22). These values are highly relevant as literary appreciation materials in senior high schools, particularly within the Merdeka Curriculum, as they support the development of students’ character. Through the TPACK approach, these values can be integrated with technology and creative pedagogical strategies, making learning more contextual, engaging, and meaningful.